Wheat yield and irrigation water productivity in a Cerrado region of Minas Gerais, Brazil - Ferreira Borges Júnior, João Carlos (Revista Ceres, 2025)
There is significant potential for expanding the wheat production chain in the Brazilian Cerrado. Studies addressing wheat crop performance in this region could help guide this expansion. This study hypothesizes that deficit irrigation can enhance irrigation water productivity without compromising wheat yield in the Cerrado region of Minas Gerais state. The aim was to evaluate the grain crop yield (Y), yield components, and irrigation water productivity (WIRRI) of two wheat cultivars under different irrigation depths. The field experiment was carried out in a 2 x 5 factorial scheme with two cultivars (BRS 404 and ORS Feroz) in combination with five irrigation levels (120%, 100%, 80%, 60% and 40% replacement of crop evapotranspiration, ETc). The cultivar BRS 404 showed the highest plant height and highest thousand grain weight. ORS Feroz presented the highest number of ears m-2. WIRRI and Y, as well as most components of yield, differed significantly depending on the irrigation level. The 54.4% reduction in total net irrigation depth caused a 29.1% reduction in yield but provided a 51.7% increase in irrigation water productivity. The adoption of deficit irrigation proved to be a viable strategy for maintaining reasonable wheat crop yield while conserving water under the experimental conditions.